Posterior Spinal Fusion Extended to Stable Vertebra Provides Similar Outcome in Juvenile Idiopathic Scoliosis Patients Compared with Adolescents with Fusion to the Touched Vertebra. (March 2019) - Oksanen, H.; Lastikka, M.; Helenius, L.; Pajulo, O.; Helenius, I.
Background and Aims: To compare outcomes between posterior spinal fusion of juvenile idiopathic scoliosis and adolescent idiopathic scoliosis patients with a minimum of 2-year follow-up. The juvenile idiopathic scoliosis patients were fused to the stable vertebra and adolescent idiopathic scoliosis to the touched vertebra. We hypothesized that extending the spinal fusion to the stable vertebra in juvenile patients would provide similar outcomes compared with fusion to the touched vertebra in adolescents. Materials and Methods: A prospective comparative study of 21 consecutive children with juvenile (Risser 0) and 84 adolescent (Risser ⩾2) idiopathic scoliosis (1:4 ratio) undergoing bilateral segmental pedicle screw instrumentation and direct vertebral derotation with a minimum of 2-year follow-up. Results: Juvenile patients had a significantly larger main curve (58° vs 53°, p = 0.003), more fused levels (p = 0.012) and posterior column osteotomies (p = 0.014) than adolescent patients. Distal adding-on (>10°) was observed in one (4.7%) juvenile and three (3.6%) adolescent patients (p = 0.80), without the need for revisions. Scoliosis Research Society 24 total score averaged 101 in juvenile and 97 in adolescent group at 2-year follow-up (p = 0.047). Conclusion: Posterior spinal fusion with bilateral segmental pedicle screw instrumentation to the stable vertebra provides similar clinical and radiographic outcomes in juvenile patients as compared with adolescents with fusion to the touched vertebra in idiopathic scoliosis. Health-related quality of life as measured using the Scoliosis Research Society 24 questionnaire at the end of follow-up was better in the juvenile as compared with the adolescent group.